Efficacy of Electroconvulsive Therapy for Neuropathic Pain Comorbid with Major Depression. (6th December 2020) - Ueda, Masashi; Konishi, Yuki; Sakurai, Kohei; Ikenouchi, Atsuko; Yoshimura, Reiji
Abstract : We report a case of a 41-year-old male with postinjury neuropathic pain comorbid with major depression in which electroconvulsive therapy (ECT) was effective in relieving both neuropathic pain and major depression. A total of 12 sessions of bilateral ECT were performed using a Thymatron® (Somatics LLC; Lake Bluff, IL). After ECT, the patient was subsequently maintained on paroxetine, eszopiclone (2 mg/day), and alprazolam. There was no relapse for at least one year after the last ECT. This case indicates that ECT might be an alternative treatment for major depression associated with chronic neuropathic pain after traumatic injury.